Investigating the evolution of merger remnants from the formation of gas disks. Issue Volume 10:Issue S309(2014) (9th February 2015) - Ueda, Junko; Iono, Daisuke; Yun, Min S.; Crocker, Alison F.; Narayanan, Desika; Komugi, Shinya; Espada, Daniel; Hatsukade, Bunyo; Kaneko, Hiroyuki; Matsuda, Yuichi; Tamura, Yoichi; Wilner, David J.; et al.
Abstract: Our new compilation of interferometric CO data suggests that nuclear and extended molecular gas disks are common in the final stages of mergers. Comparing the sizes of the molecular gas disk and gas mass fractions to early-type and late-type galaxies, about half of the sample show similar properties to early-type galaxies, which have compact gas disks and low gas mass fractions. We also find that sources with extended gas disks and large gas mass fractions may become disk-dominated galaxies.